Zero Liquid Discharge and Resource Treatment of Low-Salinity Mineralized Wastewater Based on Combing Selectrodialysis with Bipolar Membrane Electrodialysis - Xueting Zhao; Xinhao Cheng; Jinshan Sun; Jialin Liu; Zhaofeng Liu; Yali Wang; Jiefeng Pan (Separations, 2023)
A large amount of mine water is generated during coal production, which not only damages the surface environment and ecology but also wastes groundwater resources in the mining area, exacerbating regional water scarcity. In this work, a novel zero liquid discharge technology combining selectrodialysis (SED) and bipolar membrane electrodialysis (BMED) was developed for the resourceful treatment of low-salinity mineralized wastewater. The SED stack had demonstrated to be workable for the elimination of multivalent ions. The BMED stack converts brine into acid and base. After SED, a high pure crude salt (~98%) was attained. Furthermore, under the conditions of a current density of 20 mA/cm2, a flow velocity of 20 L/h, and an initial acid/base concentration of 0.10 mol/L, the maximum concentrations of acid and base were found to be 0.75 mol/L and 0.765 mol/L, respectively, for a feed conductivity of 55 mS/cm. The cost of the entire electrodialysis stage was evaluated to be USD 1.38/kg of NaOH. Therefore, this combined UF-RO-SED-BMED process may be an effective strategy for the sustainable treatment of low-salinity mineralized wastewater.